River otter and mink occupancy dynamics in riparian systems. Issue 7 (11th August 2019) - Holland, Angela M.; Schauber, Eric M.; Nielsen, Clayton K.; Hellgren, Eric C.
ABSTRACT: Semi‐aquatic mammals are dependent upon streams and riparian areas, which are a product of the landscapes they drain. Both local stream morphology and surrounding land use are likely to have important influences on current occupancy of semi‐aquatic mammals and potentially affect future geographic distributions. We identified aspects of the riparian system and stream structure at multiple scales that relate to the presence of river otter ( Lontra canadensis ) and mink ( Neovison vison ) to better understand how changing landscapes affect occupancy dynamics of these semi‐aquatic mammals and to facilitate future monitoring and management. We estimated multi‐season occupancy using 103 sites sampled over 6 seasonal sampling periods in southern Illinois, USA (44, 526 km 2 ) during 2012–2014. We hypothesized river otter and mink occupancy were related to multiple aspects of landscape and local habitat attributes including land cover, water availability, human disturbance, and stream characteristics. Occupancy of river otter was predicted by large stream size, less developed area near the stream site, and proximity to areas with reintroduced or remnant populations of river otter. Mink were more likely to occupy sites with small streams and decreased water availability near the site. However, top models for both species had low weights and high uncertainty for multiple variables. Habitat‐based models may not be the best predictors of occupancy for these carnivores because they are more likely to respond to prey diversity or availability, but landscape changes that decrease natural water availability and increase human disturbance to the stream at the local scale are likely to negatively affect river otter. © 2019 The Authors. The Journal of Wildlife Management published by Wiley Periodicals, Inc. on behalf of The Wildlife Society. Abstract : River otter and mink occupancy varied with measurements of water availability, such as stream size and percent water at the local or landscape scale. Both species responded to variation in percent developed land cover; however, for mink occupancy these results were conflicting at different scales with a positive relationship at the local scale and a negative relationship at the landscape scale. Incorporation of both habitat and prey availability measures and increased understanding of how these aspects of riparian systems interact, may lead to more effective management of river otter and mink.